REVITALISASI ISLAM KULTURAL - M. Mukhsin Jamil (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
This research aims to explore one of Islamic movements in Indonesia after reformation of 1998. By using qualitative method, it is clear that the demarcation betweeen Islamic tradisionalism and Islamic modernism fluided culturally. Although at the same time polarization both become more political, which is made Indonesian Islamic mainstream loosed elan vital as sosial and cultural movement. There is the contradictory trends in the dynamic of Islamic thought and movement introduced by Islamc minority groups. In one side the trends are multiculturalism, anti coruption movement and appreciation to the local cultures which is ignorenced before by Islamic movement in Indonesia. In other side, political oriented in many Islamic movement is stronger. The dominant of traditional constructions of Islamic polical thought of sunni (fiqh al-siyasah) influenced to the Islamic movement to state orientation at same time ignored the society with their problem and cultural expression. The cultural Islam proposed new understanding to Islamic traditions with hermeneutic and remove the locus of movement forum political Islam to civil Islam.